Human Papillomavirus Vaccine Course Completion Among Gay and Bisexual Men Who Have Sex With Men From a Time-Limited HPV Vaccination Catch-Up Program in Victoria, Australia - Htaik, Kay; Fairley, Christopher K.; Chen, Marcus Y.; Wigan, Rebecca; Rodriguez, Elena; Bradshaw, Catriona S.; Chow, Eric P. F. (Frontiers in Public Health, 2021)
Background: To examine completion of the human papillomavirus (HPV) vaccination 3-dose regimen and factors associated with completion among men who have sex with men (MSM) aged ≤26 years participating in a time-limited HPV catch-up vaccination program in Victoria, Australia. Methods: MSM who received their first dose of HPV vaccine at Melbourne Sexual Health Centre in 2017 were followed until October 2019. Vaccination completion was defined as those who received three doses. Multivariable logistic regression was performed to examine factors associated with vaccine completion. Results: 931 of 1947 (47.8%) eligible men received at least one dose of HPV vaccine, 750 (38.5%) received two and 590 (30.3%) received three doses. The median time to receiving the second and third dose was 2.8 (IQR=2.1-4.8) and 7.2 (IQR=6.3-10.7) months, respectively. Gay men had higher odds of receiving three doses compared to bisexual men (aOR=2.17; 95%CI: 1.16-4.04). Compared with HIV-negative MSM not taking PrEP, HIV-positive MSM were more like to complete vaccination (aOR=3.92, 95%CI: 1.62-9.47) but no difference was found compared to HIV-negative men taking PrEP (aOR=1.55; 95%CI: 0.95-2.53). Conclusion: Less than one-third of men aged ≤26 years completed the three doses of HPV vaccine. Further studies are needed to understand the barriers of men not completing the vaccine.